The organization and evolution of transfer RNA genes in Mycoplasma capricolum. - Muto, A (1990)
The genes for presumably all the tRNA species in Mycoplasma capricolum, a derivative of Gram-positive eubacteria, have been cloned and sequenced. There are 30 genes encoding 29 tRNA species. This number is the smallest in all the known genetic systems except for mitochondria. The sequences of 9 tRNA genes of them have been previously reported (1-3). Twenty-two genes are organized in 5 clusters consisting of nine, five, four and two genes (2 sets), respectively. The other eight genes exist as a single transcription unit. All the tRNAs are encoded each by a single gene, except for the occurrence of two tRNA(Lys)(TTT) genes. The arrangement of tRNA genes in the 9-gene cluster, the 5-gene cluster, the 4-gene cluster and one of the 2-gene clusters reveals extensive similarity with a part of the 21-tRNA gene cluster and/or the 16-tRNA gene cluster in Bacillus subtilis, respectively. The results suggest that the present M. capricolum tRNA genes have evolved from large tRNA gene clusters in the ancestral Gram-positive bacterial genome common to M. capricolum and B. subtilis, by discarding genes for redundant as well as non-obligate tRNAs, so that all the codons may be translated by as small a number of tRNAs as possible.